Percepciones estudiantiles sobre la enseñanza de ética y filosofía de la ciencia en un colegio científico en Costa Rica (Revista Lusófona de Educação, 2026)
Students’ perceptions of the teaching of ethics and philosophy of science in a scientific school in Costa RicaAbstract: This paper presents the results of a qualitative research study with an exploratory case study approach, structured around the question: What are the perceptions of six students regarding the teaching and learning process of ethics and philosophy of science at the Colegio Científico de San Carlos in 2024? The data collection techniques used were semi-structured interviews, analysis of student essays, and classroom observations. The information was inductively coded, and thematic analysis was applied to interpret the data. The findings were organized into four themes: initial perceptions of the course, teaching and learning dynamics, identified benefits, and recommendations. The research results suggest that the subject served as a bridge between the sciences and humanities, fostered self-awareness and ethical consciousness, and that students positively value ethical and philosophical reflection on science as part of their education.Keywords: Philosophy education; Secondary education; Learning; Case study; Pedagogical research.